Hadith #2785 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
Ubaydullah ibn Salman reported on the authority of a man from the Companions of the Prophet (ﷺ): When we conquered Khaybar, they (the people) took out their spoils which contained equipment and captives. The people began to buy and sell their spoils. When the Messenger of Allah (ﷺ) prayed, a man came to him and said: Messenger of Allah, I have gained today so much so that no one gained from this valley. He asked: Woe unto you, how much did you gain? He replied: I kept on selling and buying u
Grade: Da'if

Hadith #3101 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Yonus bin Abi Ishaq يونس بن أبي إسحاق; Zayd bin Arqam (Sunan Abi Dawud)
When Sa’d b. Mu’adh suffered affliction on the day of Trench (i.e. the battle of Trench) a man shot an arrow in the vein of his hand. The Messenger of Allah (ﷺ) pitched a tent for him the mosque so that he might visit him from near.
Grade: Sahih

Hadith #3869 - Sunan Abi Dawud - Abu Hurairah; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Mujahid bin Jabir مجاهد بن جبر; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: If I drink an antidote, or tie an amulet, or compose poetry, I am the type who does not care what he does. Abu Dawud said: THis was peculiar to the Prophet (ﷺ), but some people have allowed to use it, i.e. antidote.
Grade: Da'if

Hadith #4157 - Sunan Abi Dawud - Abu Hurairah; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Mujahid bin Jabir مجاهد بن جبر; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
Maimunah, wife of the Prophet (ﷺ) reported him as saying: Gabriel (peace be upon him) promised to visit me last night, but he did not visit me. Then it occurred to him that there was a pup under his bed. So he ordered and it was turned out. He then got water in his hand and sprinkled it on its place. When Gabriel (ﷺ) met him, he said: We do not enter a house which contains a dog or a picture. When the morning came, the Prophet (ﷺ) ordered to kill dogs. He ordered to kill the dog which guar
Grade: Sahih

Hadith #4341 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hilal bin Khbab هلال بن خباب; Ikrama عكرمة; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
I asked AbuTha’labah al-Khushani: What is your opinion about the verse “Care for yourselves”. He said: I swear by Allah, I asked the one who was well informed about it; I asked the Messenger of Allah (ﷺ) about it. He said: No, enjoin one another to do what is good and forbid one another to do what is evil. But when you see niggardliness being obeyed, passion being followed, worldly interests being preferred, everyone being charmed with his opinion, then care for yourself, and leave alone
Grade: Hasan

Hadith #4997 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Nu'man bin Bashir ibn Sa'd; al-Yzar bin Hryth al-Bdy al-Kwfy العيزار بن حريث; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Yahya bin Ma'in يحيى بن معين; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
Messenger of Allah! I have a fellow-wife; will it be wrong for me to boast of receiving from my husband what he does not give me? He replied: the one who boasts of receiving what he has not been given is like him who has put on two garments of falsehood.
Grade: Sahih